2014
DOI: 10.1371/journal.pone.0085068
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Association of Metabolic Syndrome and Its Components with Age-Related Cataract: The Korea National Health and Nutrition Examination Survey 2008-2010

Abstract: PurposeTo explore the relationship of the metabolic syndrome (MetS) and its components with age-related cataract in a representative Korean population.MethodsWe analyzed the data from the Korea National Health and Nutrition Examination Surveys (2008–2010). A total of 11,076 adults (4,811 men and 6,265 women) aged 40 and over who completed ophthalmologic examination were evaluated. Cataract was defined as the presence of cortical, nuclear, anterior (sub)capsular or posterior subcapsular cataract, from slit-lamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
8
25
0
Order By: Relevance
“…10,22,23 However, some studies reported a higher prevalence in women. 24,25 We found that workers with MSx had a higher mean age than those without. Other surveys conducted in Iran and other countries also showed the increasing trend in the prevalence with age.…”
Section: Discussionmentioning
confidence: 68%
“…10,22,23 However, some studies reported a higher prevalence in women. 24,25 We found that workers with MSx had a higher mean age than those without. Other surveys conducted in Iran and other countries also showed the increasing trend in the prevalence with age.…”
Section: Discussionmentioning
confidence: 68%
“…[22][23][24][25][26] Briefly, ophthalmology residents performed comprehensive slitlamp eye examinations using a BQ 900 slitlamp (Haag-Streit AG). The standard Lens Opacities Classification Systems III (LOCS III) was used to assess cataracts.…”
Section: Age-related Cataract Assessmentsmentioning
confidence: 99%
“…Our results are consistent with our previous prospective cohort study among middle-aged and elderly women in Sweden on the association between METS and cataract extraction (Lindblad et al 2008). Two previous crosssectional studies, one from Korea (Park et al 2014) and one from Lithuania (Paunksnis et al 2007) reported a significant association between METS and cataract among women but not among men.…”
Section: Discussionmentioning
confidence: 93%
“…Two previous cross‐sectional studies, one from Korea (Park et al. ) and one from Lithuania (Paunksnis et al. ) reported a significant association between METS and cataract among women but not among men.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation